Multi-Agent-Based Simulation X International Workshop, MABS 2009, Budapest, Hungary, May 11-12, 2009 Revised Selected Papers - Tosto, Gennaro.; Dyke Parunak, H. (Lecture Notes in Computer Science, 2010)
This volume contains a selection of the papers presented at the 10th International Workshop on Multi-Agent-Based Simulation (MABS 2009), a workshop co-located with the 8th International Conference on Autonomous Agents and Multiagent Systems (AAMAS 2009), which was held on May 10-15, 2009 in Budapest, Hungary.